2021
DOI: 10.1128/spectrum.00733-21
|View full text |Cite
|
Sign up to set email alerts
|

Serological Assays for Assessing Postvaccination SARS-CoV-2 Antibody Response

Abstract: Commercial serological assays for severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) are now widely available. This study adds new knowledge regarding the optimization of these assays for evaluating postvaccination antibodies status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 44 publications
1
12
0
1
Order By: Relevance
“…However, previous studies have shown that neutralizing antibody levels are highly predictive of immune protection from symptomatic SARS-CoV-2 infections. 23 Although a number of studies have demonstrated that the widely used Roche Elecsys anti-SARS-CoV-2 S immunoassay correlates with neutralizing anti-SARS-CoV-2 antibody assays, [24][25][26][27] we cannot completely exclude the possibility that results with other assays measuring directly neutralizing activity would differ in our cohorts.…”
Section: Discussionmentioning
confidence: 92%
“…However, previous studies have shown that neutralizing antibody levels are highly predictive of immune protection from symptomatic SARS-CoV-2 infections. 23 Although a number of studies have demonstrated that the widely used Roche Elecsys anti-SARS-CoV-2 S immunoassay correlates with neutralizing anti-SARS-CoV-2 antibody assays, [24][25][26][27] we cannot completely exclude the possibility that results with other assays measuring directly neutralizing activity would differ in our cohorts.…”
Section: Discussionmentioning
confidence: 92%
“…The neutralizing antibody is undoubtedly the best choice for monitoring vaccine protection, and their detection results are subject to VNT and pVNT. However, the complexity of the procedure and the length of time it takes to complete limit its widespread application ( 14 ). Relatively, CLIA is a rapid and stable method, which is widely used in the early stage of COVID-19 outbreak ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Currently, virus neutralization tests (VNTs) are utilized as the primary standard method for assessing neutralizing antibody levels ( 13 ), but due to their complex operations, high cost, and special facility requirements, pseudovirus neutralization tests (pVNTs) are served as substitutions for VNTs. However, neither of these two methodologies has received a widespread promotion, as the cost of performance for pVNTs is still too expensive, both in money and time, for ordinary clinics to afford ( 14 ). In contrast, CLIA provides high-throughput, rapid, and reproducible assays for neutralizing antibodies, as well as detecting trends and influencing variables in IgM, IgG, IgA, RBD, and neutralizing antibody levels after vaccination.…”
Section: Introductionmentioning
confidence: 99%
“…The main characteristics of this retrospective observational SARS-CoV-2 serosurveillance study have been described elsewhere [3] . Briefly, the anti-SARS-CoV-2 spike trimeric IgG were measured with DiaSorin Trimeric spike IgG immunoassay on Liaison XL (DiaSorin, Saluggia, Italy) [4] in healthcare workers undergoing primary vaccination with Pfizer/BioNTech BNT162b2 (Pfizer Inc., New York, US; two 30 µg-doses, with 3-week interval) followed by administration of homologous vaccine booster (30 µg single-dose) more than 8 months later. Molecular testing for detecting symptomatic and asymptomatic SARS-CoV-2 infections (Seegene Allplex SARS-CoV-2 Assay; Seegene Inc., South Korea or Altona Diagnostics RealStar SARS-CoV-2 RT-PCR Kit; Altona Diagnostics GmbH, Hamburg, Germany) was conducted at 2-4 weeks intervals by nasopharyngeal swab, throughout the study.…”
Section: Methodsmentioning
confidence: 99%